Surface Modification Using Prussian Blue-Gold (I)-Palladium Nanocomposite: Towards Bioelectrocatalytic Probing of Hydrogen Peroxide - Pandey P.C.; Pandey A.K. (My University, 2025)
The synthesis of functional Prussian blue-gold(I) suspension is reported which allow the formation of Prussian blue-gold(I)/gold-palladium nanocomposite on the addition of gold nanoparticles (AuNPs) and nanostructured palladium under ambient conditions. The first step involves the synthesis of PB-Au(I) suspension following facile chemical method by the addition of an aqueous solution of tetrachloroauric acid (HAuCl4) to an aqueous solution of potassium ferricyanide followed by ultrasonication. The suspension of PB-Au(I) after drying is converted into a blue-colored nanocomposite powder showing efficient bio-electrocatalysis. The presence of Au(I) is proved from X-ray photon spectroscopy. The PB-Au(I) suspension undergo nanocomposite formation with gold and palladium nanoparticles. Such nanocomposites are formed by allowing ultrasonication of gold nanoparticles (AuNPs) or palladium that ultimately lead to the formation of three different electrocatalytic material designated as: (1) PB-Au(I), (2) PB-Au(I).AuNPs, and (3) PB-Au(I)/AuNPs-Pd and used for the development of efficient hydrogen peroxide sensors based on graphite paste-modified electrodes. Three different systems of modified electrodes namely PB-Au(I), PB-Au(I)/AuNPs, and PB-Au(I)/AuNPs-Pd are made by mixing the composite materials, graphite powder, binder in absence and the presence of horseradish peroxidise. The performance of these modified electrodes based on electrochemical measurement suggests gradual improvement in electrocatalysis in order of PB-Au(I)/AuNPs-Pd>PB-Au(I)/AuNPs>PB-Au(I)>PB. The results of cyclic voltammery and amperometric measurements are reported in this communication. The sensitivity for H2O2 determination is found to be order of 617.3 μAmM-1cm-2 with a detection limit of 0.1 μM for PB-Au(I)/AuNPs-Pd-modified electrode. The stability of the modified electrodes is found to be more than 3 months. © Springer Science+Business Media, LLC 2012.